Severe Plasmodium falciparum malaria is associated with circulating ultra-large von Willebrand multimers and ADAMTS13 inhibition. - Deirdre Larkin; Bas de Laat; P Vince Jenkins; James Bunn; Alister G Craig; Virginie Terraube; Roger J S Preston; Cynthia Donkor; George E Grau; Jan A van Mourik; James S O'Donnell (PLoS Pathogens)
Plasmodium falciparum infection results in adhesion of infected erythrocytes to blood vessel endothelium, and acute endothelial cell activation, together with sequestration of platelets and leucocytes. We have previously shown that patients with severe infection or fulminant cerebral malaria have significantly increased circulatory levels of the adhesive glycoprotein von Willebrand factor (VWF) and its propeptide, both of which are indices of endothelial cell activation. In this prospective study of patients from Ghana with severe (n = 20) and cerebral (n = 13) P. falciparum malaria, we demonstrate that increased plasma VWF antigen (VWF:Ag) level is associated with disproportionately increased VWF function. VWF collagen binding (VWF:CB) was significantly increased in patients with cerebral malaria and severe malaria (medians 7.6 and 7.0 IU/ml versus 1.9 IU/ml; p<0.005). This increased VWF:CB correlated with the presence of abnormal ultra-large VWF multimers in patient rather than control plasmas. Concomitant with the increase in VWF:Ag and VWF:CB was a significant persistent reduction in the activity of the VWF-specific cleaving protease ADAMTS13 (approximately 55% of normal; p<0.005). Mixing studies were performed using P. falciparum patient plasma and normal pooled plasma, in the presence or absence of exogenous recombinant ADAMTS13. These studies demonstrated that in malarial plasma, ADAMTS13 function was persistently inhibited in a time-dependent manner. Furthermore, this inhibitory effect was not associated with the presence of known inhibitors of ADAMTS13 enzymatic function (interleukin-6, free haemoglobin, factor VIII or thrombospondin-1). These novel findings suggest that severe P. falciparum infection is associated with acute endothelial cell activation, abnormal circulating ULVWF multimers, and a significant reduction in plasma ADAMTS13 function which is mediated at least in part by an unidentified inhibitor.